2015
DOI: 10.3892/br.2015.431
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the combination of vitamin K and teriparatide on the bone metabolism in ovariectomized rats

Abstract: Abstract. The purpose of the present study was to evaluate the combined effects of vitamin K (VK) and teriparatide (TPTD) on bone mineral density (BMD), mechanical strength and other parameters for bone metabolism using a rat ovariectomized osteoporosis model. Ovariectomized female Sprague-Dawley rats were administered with VK (an oral dose of 30 mg/kg/day), TPTD (a subcutaneous dose of 30 µg/kg, three times a week) or a combination for 8 weeks. Thereafter, serum levels of γ-carboxylated osteocalcin (Gla-OC) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…A recent study has also suggested that VK supplementation enhanced BMD and bone strength improvements induced by teriparatide treatment [83].…”
Section: Vitamin K and Bone Qualitymentioning
confidence: 97%
“…A recent study has also suggested that VK supplementation enhanced BMD and bone strength improvements induced by teriparatide treatment [83].…”
Section: Vitamin K and Bone Qualitymentioning
confidence: 97%
“…Several animal models have been used to study the effects of vitamin K on the bone metabolism. The studies on ovariectomized rats [ 44 , 62 , 64 ], on unilaterally sciatic neurectomized rats [ 65 , 66 ], and in tail-suspended rats [ 67 , 68 ] found that vitamin K treatment had significant positive effects on the bone health. Histologic and microcomputed tomographic evaluations demonstrated that vitamin K2 supplementation inhibited the loss of bone mass density and trabecular bone, improved osteoblast function, and enhanced the serum level of the bone anabolic markers.…”
Section: Effects Of Vitamin K On Different Osteoporotic Rat Modelsmentioning
confidence: 99%
“…Coadministration of vitamin K2 and Teriparatide (low dose parathyroid hormone derived peptide) improved the osteoblast function and increased the serum level of Gla-OC. These effects were greater in combined use compared to the occasion when vitamin K2 and TPTD were administered in isolation [ 64 ].…”
Section: Effects Of Vitamin K On Different Osteoporotic Rat Modelsmentioning
confidence: 99%
“…Table 2 reports the main in vivo studies with VK and its association with bone remodeling. The treatment of ovariectomized [ 139 , 140 ], unilaterally sciatic neurectomized [ 38 ], and tail suspended rats [ 141 ] with VK found positive effects on bone health. Histologic and microcomputed tomographic evaluations demonstrated that VK2 supplementation inhibited the loss of bone mass as well as improved OB function and bone architecture.…”
Section: Vitamin K and Vitamin D In Bone Remodeling—in Vivo Studiementioning
confidence: 99%
“…Some animal studies investigated the effect of the coadministration of VK2 and other bone acting drugs on osteoporosis. The coadministration of VK2 and Teriparatide improved OB function and increased Gla-OC serum levels [ 140 ]. The effect of the combined use of VK2 and bisphosphonate showed that VK2 could ameliorate the suppressive effect of bisphosphonates on bone turnover and increase bone volume as well as the bone formation parameters [ 143 ].…”
Section: Vitamin K and Vitamin D In Bone Remodeling—in Vivo Studiementioning
confidence: 99%